24-hour efficacy of the bimatoprost–timolol fixed combination versus latanoprost as first choice therapy in subjects with high-pressure exfoliation syndrome and glaucoma. Issue 7 (18th May 2013) - Konstas, Anastasios-Georgios P; Holló, Gábor; Mikropoulos, Dimitrios G; Haidich, Anna-Bettina; Dimopoulos, Antonios T; Empeslidis, Theodoros; Teus, Miguel A; Ritch, Robert
Abstract : Aim: To compare the 24-h intraocular pressure (IOP) control obtained with the bimatoprost–timolol fixed combination (BTFC) versus latanoprost in newly diagnosed, previously untreated exfoliation syndrome (XFS) or exfoliative glaucoma (XFG) patients with baseline morning IOP greater than 29 mm Hg. Methods: One eye of 41 XFS/XFG patients who met inclusion criteria was included in this prospective, observer-masked, crossover, comparison protocol. All subjects underwent a 24-h untreated curve and were then randomised to either evening administered BTFC or latanoprost for 3 months and then switched to the opposite therapy. At the end of each treatment period, patients underwent a treated 24-h IOP assessment. Results: 37 patients completed the trial. At baseline, mean untreated 24-h IOP was 31.1 mm Hg. Mean 24-h IOP with BTFC was significantly lower than with latanoprost (18.9 vs 21.2 mm Hg; p<0.001). Furthermore, BTFC reduced IOP significantly more than latanoprost at every time point, for the mean peak and trough 24-h IOP (p<0.001). There was no difference, however, in mean 24-h IOP fluctuation between the two medications (3.8 with BTFC vs 4.2 with latanoprost; p=0.161). Both treatments were well tolerated and there was no statistically significant difference for any adverse event between them. Conclusions: As first choice therapy in high-pressure, at-risk exfoliation patients, BTFC controlled mean 24-h IOP significantly better than latanoprost monotherapy.